IMPLEMENTATION OF THE TQM SYSTEM IN UKRAINIAN ENTERPRISES - TANASIIENKO, Nataliia; НOLOVACH, Tetiana; ZABOLOTNA, Sofiia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article substantiates the feasibility of using an innovative system of total quality management (TQM) based on theoretical and methodological research. This system has proven its effectiveness in the global economic space. It helps to solve problems associated with increasing the production of high-quality products, the interest and motivation of employees, and also makes production management more effective. The experience of introducing this system by individual countries, in particular, Japan and the USA, is also considered. A comparison of the indicators of Japanese companies before and after the implementation of the TQM model is given.It was concluded that today the majority of domestic enterprises manage product quality in accordance with the principles of the ISO 9000 series. ISO standards are based on technical systems and procedures, but employee involvement and continuous improvement are optional. Unlike ISO, the TQM system involves prioritizing philosophy, concepts, tools and methodology, as well as involvement of all employees and a continuous improvement of quality. The possibility of adapting the TQM system to the practice of Ukrainian enterprises was investigated. Given the available resource potential, this is possible, but first of all, for this, it would be necessary to completely rethink the approach to the management of the organization and conduct trainings on familiarizing employees with the TQM system. Based on the analysis of the main technical and economic indicators of the « Agricultural company 2004» PE, it is proposed to apply the key principles of TQM, which were developed by the famous scientist E. Deming, to increase the efficiency of its activities.
Keywords: TQM; quality; competitiveness; enterprise; TQM principles